O2-S5.06 Health-seeking behaviours among female sex workers in a community randomised trial in Peru (The Peru-PREVEN Study). (10th July 2011) - Kohler, P; Campos, P E; Buendia, C; Carcamo, C; Garcia, P J; Hughes, J; Mejia, C; Garnett, G; Holmes, K
Abstract : Background: This study aims to evaluate health-seeking and HIV/STD preventive behaviours among FSW in mid-sized cities in Peru associated with a community randomised trial intervention and with venue of sex work. Methods: Through the Peru PREVEN multi-component intervention, mobile team outreach to FSW was conducted in an effort to lower STD rates and increase condom use as well as care-seeking from local Ministry of Health clinics for screening and evaluation of STDs. Relative risks for behavioural outcomes were calculated using multivariate Poisson regression models with robust standard errors and accounting for clustering by city. Analyses were adjusted for city-specific baseline outcomes and by brothel venue, as there were a higher proportion of brothels in intervention cities. A sub-analysis of outcomes associated with brothel venue did not control for baseline but did adjust for age, marital/cohabitation status, alcohol use, geographical region, education and randomisation arm. Results: 4156 FSW were enrolled in 20 cities; 2063 from control and 2093 from intervention cities. The median age at first paid sex was 21 years and the median duration of sex work was 20 months. Sex work was relatively frequent, with a median of 6 days worked in the last week, 4 weeks in the last month and 8 months in the last year. Frequency of sex work increased with age (p<0.001). Twenty-one per cent of FSW were brothel based, 23% street based and 56% were bar or nightclub based. Although proportions of care-seeking behaviours were higher in intervention cities, differences were not statistically significant. In evaluating relationships of venue and health-seeking behaviours, brothel-based FSW reported significantly lower rates of non-condom use with clients (RR=0.18; 95% CI 0.07% to 0.44%), and higher rates of recent health screening exams (RR=1.97; 95%CI 1.58% to 2.45%) and of HIV testing in the last year (RR=1.74; 95% CI 1.45% to 2.09%), compared with FSW who were street or bar-based. Brothel-based FSW also more frequently reported knowledge of STDs (RR=1.07; 95% CI 1.04% to 1.09%) and recognition of STD symptoms in women (RR=1.39; 95%CI 1.22% to 1.59%) and in men (RR=1.32; 95% CI 1.12% to 1.57%). Conclusions: Sex work venue is significantly associated with the health care-seeking and STD preventive behaviours of sex workers. Interventions to promote STD detection and prevention among FSW should consider structural or regulatory factors related to sex work venue.